(untitled) (Experimental biology, 2018)
The sunflower collection of LLС "Experimental Farm oilseeds" of Eastern Kazakhstan region was studied, including 36 lines with cytoplasmic male sterility (line A), 44 lines fixers of sterility (line B), 43 reducing pollen fertility lines (line R) on the basis of: weight of 1000 seeds, the percentage of the huskness, filling of grain, oil and free proline content of seeds. Analysis of the data on the studied traits showed that studied sunflower samples are characterized by wide amplitude variation. Data on the elements of productivity and qualitative lines of sunflower seeds were processed by the method of cluster analysis. According to the evaluation of results database of indicators of seed to be used in breeding of hybrid was established. 29 sunflower lines that can be used as sources of economically valuable traits was allocated. Analysis of the free proline content in seeds of inbred lines allowed them to be divided into 3 groups: low-proline content in seeds (30 to 50 mg /%), mid level of proline content (51 to 80 mg /%) and high proline content lines ( from 81 mg /% and above). Correlation analysis of the level of free proline data in seeds and the length of the growing season showed a weak positive correlation between these indicators: r = 0,28 in lines of group A and 0.28 in lines of group B, the most significant positive correlation is found in lines of group R (r = 0,45).